The conceptualization of political metaphors on Medan-Indonesia mass media - Surip, M.; Rohim, Syaiful; Gafari, M. Oki Fardian (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
The purpose of this study seeks to analyze the conceptualization of political metaphors contained in political discourse in mass media in Medan-Indonesia. The problem analyzed is how to conceptualize political metaphors in national mass media (waspada.go.id, medan.tribunnews.com, sumut.antaranews.com, and hariansib.com). The main theory used to discuss this research problem uses the conceptual metaphorical theory/CMT of Lakoff, Johnson, and Kövecses. This research uses qualitative descriptive methods, with methods using basic referential techniques. The total data is 15, sorted according to CMT theory. The results of the study found that the conceptualization of political metaphors in the mass media in Indonesia is divided into 4 mapping domains, namely: war domain mapping, religious, mystical/occult, and animal. The conceptualization of political metaphors in the mass media explains the manifestation of political reality in society. Politics is conceptualized into warfare, the religious reality of society, the unseen and the reality of the bad picture of politicians.